Gang membership and marijuana use among African American female adolescents in North Carolina - Wechsberg WM; Doherty IA; Browne FA; Kline TL; Carry MG; Raiford JL; Herbst JH (Dove Medical Press, 2015)
Wendee M Wechsberg,1–4 Irene A Doherty,1 Felicia A Browne,1,5 Tracy L Kline,1 Monique G Carry,6 Jerris L Raiford,6 Jeffrey H Herbst6 1Substance Abuse Treatment Evaluations and Interventions Research Program, RTI International, Research Triangle Park, 2Gillings Global School of Public Health, University of North Carolina, Chapel Hill, 3Psychology in the Public Interest, North Carolina State University, Raleigh, 4Psychiatry and Behavioral Sciences, School of Medicine, Duke University, Durham, NC, 5Department of Social and Behavioral Sciences, Harvard School of Public Health, Boston, MA, 6Division of HIV/AIDS Prevention, National Center for HIV/AIDS, Viral Hepatitis, STD and TB Prevention, US Centers for Disease Control and Prevention, Atlanta, GA, USA Abstract: The southeastern US sustains the highest high school dropout rates, and gangs persist in underserved communities. African American female adolescents who drop out of school and are gang members are at substantial risk of exposure to severe violence, physical abuse, and sexual exploitation. In this study of 237 female African American adolescents 16–19 years of age from North Carolina who dropped out or considered dropping out, 11% were current or past gang members. Adolescents who reported gang membership began smoking marijuana at a mean age of 13, whereas those who reported no gang membership began at a mean age of 15 years (P<0.001). The mean ages of first alcohol use were 14 years and 15 years for gang members and non-gang members, respectively (P=0.04). Problem alcohol use was high in both groups: 40% and 65% for non-gang and gang members, respectively (P=0.02). Controlling for frequent marijuana use and problem alcohol use, adolescents who reported gang membership were more likely than non-gang members to experience sexual abuse (odds ratio [OR] =2.60, 95% confidence interval [CI] [1.06, 6.40]), experience physical abuse (OR =7.33, 95% CI [2.90, 18.5]), report emotional abuse from their main partner (OR =3.55, 95% CI [1.44, 8.72]), run away from home (OR =4.65, 95% CI [1.90, 11.4]), get arrested (OR =2.61, 95% CI [1.05, 6.47]), and report violence in their neighborhood including murder (OR =3.27, 95% CI [1.35, 7.96]) and fights with weapons (OR =3.06, 95% CI [1.15, 8.11]). Gang members were less likely to receive emotional support (OR =0.89, 95% CI [0.81, 0.97]). These findings reinforce the urgent need to reach young African American women in disadvantaged communities affiliated with gangs to address the complexity of context and interconnected risk behaviors. Keywords: school dropouts, youth alcohol use, sexual abuse, physical abuse, violence, drug abuse